1992
DOI: 10.1111/j.1432-1033.1992.tb16674.x
|View full text |Cite
|
Sign up to set email alerts
|

Cloning and sequence analysis of cDNA encoding aspartate aminotransferase isozymes from Panicum miliaceum L., a C4 plant

Abstract: The cytosolic and mitochondrial isozymes of aspartate aminotransferase (AspAT) function in the C4 dicarboxylate cycle of photosynthesis. We constructed a cDNA library from leaf tissues of Panicum miliuceum, an NAD-malic-enzyme-type C4 plant and screened the library for AspAT isozymes. A full-length cDNA clone for cytosolic AspAT was isolated. This clone contains an open reading frame that encodes 409 amino acids. We also isolated two cDNA clones for different precursors of mitochondria1 AspAT. Comparing these … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
26
0

Year Published

1992
1992
2002
2002

Publication Types

Select...
5
4

Relationship

2
7

Authors

Journals

citations
Cited by 33 publications
(26 citation statements)
references
References 35 publications
0
26
0
Order By: Relevance
“…AspAT genes have been cloned from severa1 plant species, including alfalfa, Panicum, soybean, carrot, and lupin (Gantt et al, 1992;Taniguchi et al, 1992;Turano et al, 1992;Wadsworth et al, 1993). Although only one or two cDNAs have been isolated from each of these other plant species, five different AspAT cDNAs have been cloned from Arabidopsis (Sch!Atz and Coruzzi, 1995;Wilkie et al, 1995).…”
Section: Aspartate Aminotransferase: Defining Distinct Roles For Lsoementioning
confidence: 99%
“…AspAT genes have been cloned from severa1 plant species, including alfalfa, Panicum, soybean, carrot, and lupin (Gantt et al, 1992;Taniguchi et al, 1992;Turano et al, 1992;Wadsworth et al, 1993). Although only one or two cDNAs have been isolated from each of these other plant species, five different AspAT cDNAs have been cloned from Arabidopsis (Sch!Atz and Coruzzi, 1995;Wilkie et al, 1995).…”
Section: Aspartate Aminotransferase: Defining Distinct Roles For Lsoementioning
confidence: 99%
“…The amino acid sequences predicted from cDNAs for mitochondrial AAT showed that mitochondrial AAT(s) are synthesized as precursor proteins that have a 28-amino-acid presequence. 6) In spite of recent progress in studies of plant AA Ts, detailed comparative studies on enzymatic properties of the isoenzymes of plant AA T from a single plant source with homogeneously purified preparations have not been done because of difficulty in the purification of the isoenzymes of plant AAT in a large enough amount to characterize them.…”
mentioning
confidence: 99%
“…The deduced amino acid sequence of the protein encoded by the pSAT2 open reading frame and AAT amino acid sequences from several plant and animal sources were compared. The pSAT2 sequence shares the highest level of similarity with the two Panicurn mitochondrial AAT proteins [21], 81.5~o and 82.0 ~o identity, respectively and with the rat mitochondrial AAT protein [ 12], 56.1 ~o identity.…”
Section: Characterization Of Aa T Cdnamentioning
confidence: 93%
“…The deduced amino acid sequence of the pSAT2-encoded protein was aligned with the protein sequences of the soybean plastid AAT [25] and the Panicum mitochondrial AAT3 [21] (Fig. 3).…”
Section: Characterization Of Aa T Cdnamentioning
confidence: 99%